Odpowiedzi

  • Użytkownik Zadane
2009-09-21T16:50:00+02:00
C) 3(x-5y)(2x+y)=(3x-5y)(2x+y)=6x-5y
2009-09-21T17:06:18+02:00
B) (10a+3b)(7a-4b)= 70a²-40ab+21ab-12b²=70a²-19ab-12b²
c) 3(x-5y)(2x+y)= 3(2x²+xy-10xy-5y²)= 3(2x²-9xy-5y²)= 6x²-27xy-15y²
a) 7x²-2x{3x-[-by-x(y+3)-y(x+2)]}=
7x²-2x{3x-[-by-xy-3x-xy-2y]}=
7x²-2x{3x-[-by-2xy-3x-2y]}=
7x²-2x{3x+by+2xy+3x+2y}=
7x²-6x²-2bxy-4x²y-6x²-4xy=
-7x²-2bxy-4x²y-4xy
Najlepsza Odpowiedź!
2009-09-21T17:09:04+02:00
7x²-2x{3x-[-by-(xy+3x)-(xy+2x)]}=
7x²-2x[3x-(-by-xy-3x-xy-2x)]=
7x²-2x[3x-(-by-2xy-5x)]=
7x²-2x(3x+by+2xy+5x)=
7x²-6x²-2bxy-4x²y-10x²=
-9x²-2bxy-x²(4y)=
-10x²-2bxy-4y



b)(10a+3b)(7a-4b)=
70a²+21ab-40ab-12b²=
70a²-19ab-12b²


c)jak koleżanka powyżej


p.s. nie gwarantuję, że jest dobrze, radzę zaczekać na kolejną odpowiedź.